Augmented Reality tentang Pembelajaran Etika Makan - Kristian Imanuel Kuhon; Sherwin R.U.A. Sompie; Brave A. Sugiarso (Universitas Sam Ratulangi, 2022)
Abstract — Table manners are the basic rules that apply at the dining table. This rule is usually applied at formal banquets. This simple activity has a big impact on everyday life. This study aims to design and develop an application for learning about table manners to make it easier to learn the rules that need to be known in formal banquets, including etiquette before and during the process of eating food, as well as the use of cutlery. Augmented reality training method where all participants are given a lunch starting from appetizer, soup, main course to dessert. The research method used is the MDLC (Multimedia Development Life Cycle) method. From the results obtained in this study is the arrangement of an Augmented Reality-based table manners learning application that can display information along with 3D objects and animations. Keywords — Augmented Reality, Table Manner, Multimedia Development Life Cycle, Smartphone.Abstrak — Table manners adalah aturan-aturan pokok yang berlaku di meja makan. Aturan ini biasanya diterapkan pada jamuan makan resmi. Kegiatan yang sederhana ini memiliki dampak besar bagu kehidupan sehari-hari. Penelitian ini bertujuan untuk merancang dan mengembangkan suatu aplikasi pembelajaran tentang table manners untuk memudahkan dalam mempelajari aturan-aturan yang perlu diketahui dalam jamuan makan resmi, meliputi etika sebelum dan saat proses menyantap makanan, serta penggunaan alat-alat makan. Metode pelatihan augmented reality dimana seluruh partisipan diberikan jamuan makan siang mulai dari appetizer, soup, main course hingga dessert. Metode penelitian yang digunakan adalah metode MDLC (Multimedia Development Life Cycle). Dari hasil yang didapat dalam penelitian ini adalah tersusunnya suatu aplikasi pembelajaran table manners berbasis Augmented Reality yang dapat menampilkan informasi beserta objek dan animasi 3D.Kata kunci — Augmented Reality, Table Manner, Multimedia Development Life Cycle, Smartphone.